Macroeconomic determinants of foreign exchange rate exposure - Fabian U. Fuchs (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2020)
This paper examines the foreign exchange rate exposures of US companies and how they are linked to foreign macroeconomic determinants. I use US trade-weighted macroeconomic indices of foreign countries to explain the variation in foreign exchange rate exposures, measured as the sensitivities of stock returns to exchange rate returns of US non-financial companies over the period 1995 to 2017. I find strong evidence that the after-hedging exposures of potential exporters are affected by their expectations of foreign market gross domestic products, current account balances, consumer price indices, term spreads, unit labor costs as well as government expenditures.
Keywords: F31; G1; E44; 650; exchange rate exposure; macroeconomic expectations; selective hedging